Mechanical properties enhancement of cubic boron nitride by using a b4c/bcn multilayer coating system (2006)
ABSTRACT: Multilayer of B4C / BCN /c-BN were deposited on to high speed steel substrates AISI M2 by r.f. (13.56 MHz) multi-target magnetron sputtering from high purity (99.99 %) h-BN and a (99.5%) B4C targets, in an Ar (90%) / N2 (10%) gas mixture. Films were deposited at 300 o C, with r.f power density of 7 W/cm2. For their deposition we varied the bias voltage of the B4C films between –50 and –150 V and for the BCN coatings the nitrogen gas flow from 2% to 12%. A 300-nm thick TiN buffer layer was first deposited to improve the adhesion of all samples. Mechanical properties like hardness, elastic Young Modulus, and adhesion were determined by Nanoindentation and Scratch measurements. Machining test by turning of low alloyed steel bars with burins coated with 16 bilayers, enabled an increment of tools performance of 67% compared with uncoated tools.